Optimization of Laccase Productivity during Solid Substrate Fermentation of Sago Hampas by Pycnoporus sanguineus - A, Rifat; S, , Paramaswari,; Abdullah, Noorlidah; , M, Sekaran; S, Vikineswary, (Malaysian Journal of Science, 2003)
Pycnoporus sanguineus showed good growth during solid substrate fermentation (SSF) of sago pith residue known as hampas, which was supplemented with 0.38% (w/v) (63.3mM) urea as nitrogen source, 0.2% (w/v) KH_2PO_4 and 0.05% (w/v) MgSO_4.7H_20, over a period of 30 days. In unoptimized conditions using a two-week old, 10% (w/w) inoculum, maximum laccase productivity of 14.35 U/g of substrate was obtained on day 15. The productivity of laccase increased to 15.20 U/g of substrate when sago hampas was supplemented with 0.76% (w/v) (126.7mM) of urea. Further, laccase productivity was influenced by the inoculum age and density (weight of inoculum/weight of substrate). With a 3-week old inoculum at 10% density (w/w) the laccase productivity increased to 18.05 U/g of substrate after 15 days of SSF. This is an increase of 1.3 fold compared to the unoptimized value. The maximum laccase productivity obtained with the optimized conditions was 18.35 U/g of substrate on day 10 of SSF. A pH range of 4.0 Ã¢â‚¬â€ 5.0 seems to be suitable for the SSF. Laccase productivity was growth associated which correlated well with the soluble protein content measured during the course of SSF.